The associations between fatigue, apathy, and depression in Parkinson's disease. (6th October 2014) - Skorvanek, M.; Gdovinova, Z.; Rosenberger, J.; Ghorbani Saeedian, R.; Nagyova, I.; Groothoff, J. W.; van Dijk, J. P.
<x xml:space="preserve">Abstract</x> Objectives Fatigue and apathy are two of the most common and most disabling non‐motor symptoms of Parkinson's disease (PD). They have a high coincidence and can often be confused; moreover, their relationship is not fully understood. The aim of our study was to describe the coincidence of apathy with different fatigue domains in the presence/absence of depression and to separately describe the associations of different aspects of primary and secondary fatigue with apathy and other clinical and disease‐related factors. Materials and methods A total of 151 non‐demented patients with PD were examined using the Movement Disorder Society‐Unified Parkinson's Disease Rating Scale (MDS‐UPDRS), Starkstein Apathy Scale, Multidimensional Fatigue Inventory (MFI), Beck Depression Inventory‐II, and Epworth Sleepiness Scale. Results The prevalence and severity of fatigue and apathy were significantly higher in depressed PD patients. However, our results show that depression, fatigue, and apathy can be clearly distinguished in PD. Apathy was associated with the MFI's‐reduced motivation domain in both depressed and non‐depressed patients. However, apathy was associated with mental fatigue aspects only in non‐depressed patients, and it was not related to the physical aspects of fatigue in any of the studied groups. Conclusions Although the pathophysiology of fatigue and apathy in PD is clearly multifactorial, in a proportion of PD patients, these symptoms are associated with depression, dopaminergic depletion in the mesocorticolimbic structures, and disruption of the prefrontal cortex‐basal ganglia axis. Therefore, in some PD patients, adequate management of depression and optimal dopaminergic medication may improve both fatigue and apathy.